Differences in osteon structure histomorphometry between puppyhood and adult stages in the Golden Retriever - Korakot Nganvongpanit (2018)
© 2016, Japanese Association of Anatomists. Osteon structure has been widely studied in mammals, but osteon structure in dogs has received relatively little attention, especially in terms of whether aging has any effect on osteon structure. The aim of this study was to compare the osteon structure of both flat (scapula and os coxae) and long bones (humerus, radius, ulna, metacarpus, femur and tibia) of male puppy and adult Golden Retrievers. We examined five parameters: Haversian canal diameter, Haversian canal area, osteon diameter, osteon area, and number of lacunae per osteon. Our results show that the values for Haversian canal diameter were significantly higher in the os coxae and tibia, but significantly lower in the femur of adult dogs as compared to those of puppies. The Haversian canal diameter of the other bones investigated did not show any significant differences between puppies and adult dogs. The Haversian canal area was significantly greater in the os coxae, radius and femur of adult dogs than in those of puppies. The osteon diameter and area of every bone examined were significantly smaller in puppies than in adult dogs. Lastly, the number of lacunae per osteon showed the same trend as osteon diameter and area. Plexiform bone could be found in three bones in puppies, i.e. the femur, humerus and tibia. Overall, the results of this study should provide basic knowledge on the microanatomy of cortical bone in dogs and on the possible influence age.